The Survey of the Relationship between the Social Support and the Mental Health among the City of Tabriz Citizens in 2014 - Mohsen Hojat (Journal of Global Pharma Technology, 2017)
Objective the citizens are the focal point of the emotions and excitement, center if the joy and health, the pounding heart and the capitals of a nation and this is why the states pay a great deal of their attention to the citizens’ psychological health in the cultural and social planning and policy-making. The present study aims at the determination of the relationship between the social support and the citizens’ psychological health in the city of Tabriz in 2013. Methods The current study is an analytical-descriptive research. The study sample volume has been selected from an above-15-year old 398 individuals (200 women and 198 men) population based on a multistage clustering method in the city of Tabriz. The information collecting tools were the social support questionnaire and general psychological health questionnaire (GHQ-28). To analyze the data, there was made use of SPSS program ver.16 and the statistical tests such as linear regression tests and independent t-test. Findings According to the findings obtained through the data analyses performed in the current study it was found out that there is a significant relationship between social support and psychological health (P<0.001). The women social support is directly associated with their mental health (P=0.02). Also, there is an inverse relationship between social support with the women’s anxiety-sleep disorders symptoms (P=0.02) and the women’s intensive depression symptoms (p=0.04). Conclusion Social support is in a direct and significant relationship with the women and men’s mental health. Changing the policy making goals with the objective of enhancing the quality and the quantity of the supportive networks, particularly for the susceptible women, can cause the social supports protective effects to be corroborated.Keywords: Mental health, Social support, Gender.